Pengembangan MODUL PEMBELAJARAN TEMATIK SUBTEMA TUMBUHAN SAHABATKU DENGAN PENDEKATAN BUDAYA LOKAL BANTEN UNTUK MENAMBAH PENGETAHUAN SISWA: Di Kelas VI SD Negeri Karundang 1 Kota Serang - Nursobah, Siti; Habudin, Habudin; Mansur, Mansur (Jurnal keilmuan dan Kependidikan dasar, 2022)
This study aims to determine the development of a thematic learning module for the sub-theme of my friend plant with a local Banten culture approach to increase the knowledge of students in grade VI SD Negeri Karundang 1 Serang City. The type of research used is research development / R & D using the 4D model of S. Thiagarajan. 4D development has 4 stages, namely Define, Design, Develop, and Disseminate. The developed media was validated by material experts and media experts using an assessment rubric before conducting initial trials on students. Based on the assessment of material experts, that the product is very feasible for field trials with a score of 109 with a percentage of 87.2% (very feasible) and the assessment of media experts, that the product is very feasible for field trials with a score of 86 with a percentage of 86% (very worthy). The results of the development trial get the average number of students' knowledge of 76.6 (effective). Overall, the media for the My Friends Plants Sub-thematic Learning Module with a Banten Local Culture Approach to Increase Students' Knowledge in Grade VI SD Negeri Karundang 1 Serang City is very feasible and effective to be used as one of the learning media in teaching and learning activities in schools.